Validation of a Modified Version of Actero™ Salmonella Enrichment Media for Rapid Detection of Salmonella spp. in Environmental and Food Samples: AOAC Performance Tested MethodSM 041403. (27th February 2020) - Boumail, Afia; Eyraud, Alex; Akassou, Mounia; Geffroy, Mélanie; Sicard, Jean-Félix; Tremblay, Renaud; Olishevskyy, Sergiy
Abstract: Background: Actero™ Salmonella Enrichment Media 1 (Actero™ Salmonella) is a culture broth developed to recover Salmonella spp. from foods and environmental surfaces. Performance of Actero™ Salmonella broth has already been assessed and validated ( AOAC Performance Tested Method SM 041403) for the detection of Salmonella spp. in various foods, feeds and environmental samples. Objective: This study aimed to validate the performance of a modified version of Actero™ Salmonella broth by incorporating one of the two liquid supplements into the powdered formula. Methods: Inclusivity, exclusivity, stability, and lot-to-lot studies were carried out. Raw ground beef, chicken carcass rinse, dry pet food and stainless steel samples were enriched for 14–20 h at 35–39°C and analyzed using real-time PCR assay as well as by direct plating. Results: The Probability of Detection assay confirmed the equivalent performance of the alternative methods as compared to the reference methods. All Salmonella strains, except Salmonella II : 57: z29:-, were able to grow in Actero™ Salmonella broth. One-half of the non-target strains did not grow in Actero™ Salmonella broth, whereas the atypical for Salmonella growth was observed for other non-target microorganisms subsequently plated onto selective and differential agars. Lot-to-lot consistency was demonstrated for three consecutively manufactured lots of the broth. The liquid broth was proven to be stable at 4°C for up to 9 weeks of storage. Conclusions and Highlights: The incorporation of one of the two specific supplements into a powdered formula of Actero™ Salmonella broth made it more convenient to use without compromising the performance and accuracy.